2012
DOI: 10.1113/jphysiol.2011.222687
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic mechanisms of CO2 responses in parafacial respiratory neurons of newborn rats

Abstract: Key points• The central chemoreceptors for respiratory control in the medulla sense changes in CO 2 concentration and regulate respiratory activity.• Neurons that express a transcription factor, Phox2b, in the parafacial region of the rostral and ventrolateral medulla are excited by hypercapnic stimulation and are proposed to play an important role in central chemoreception.• In this study, we show evidence that Phox2b-expressing parafacial neurons in neonatal rats were sensitive to hypercapnia via direct acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 24 publications
4
36
0
Order By: Relevance
“…In keeping with this interpretation, RTN neurons are activated by CO 2 and acidification in coronal slices of neonate rodent brain (Fig. 5G2) even when synaptic activity is reduced by addition of blockers of glutamatergic, glycinergic, and GABAergic ionotropic transmission plus PPADS, a blocker of ATP receptors (231, 300, 355) or by incubation in low calcium/high magnesium solution (328). Finally, these cells also retain their CO 2 sensitivity after acute isolation (446) (Fig.…”
Section: The Retrotrapezoid Nucleusmentioning
confidence: 57%
See 1 more Smart Citation
“…In keeping with this interpretation, RTN neurons are activated by CO 2 and acidification in coronal slices of neonate rodent brain (Fig. 5G2) even when synaptic activity is reduced by addition of blockers of glutamatergic, glycinergic, and GABAergic ionotropic transmission plus PPADS, a blocker of ATP receptors (231, 300, 355) or by incubation in low calcium/high magnesium solution (328). Finally, these cells also retain their CO 2 sensitivity after acute isolation (446) (Fig.…”
Section: The Retrotrapezoid Nucleusmentioning
confidence: 57%
“…Numerous electrophysiological studies subsequently showed that acidification or increases in PCO 2 (10%–15%) alters the discharge rate and/or membrane potential of brainstem neurons recorded in such preparations as the whole neonatal brainstem and brain slices, usually from neonatal rodents, or in culture (76,77,167,203,300,328,447,448,458). A substantial proportion of neurons (15%–45%) selected at random within a given region are mildly activated/depolarized and a similar proportion are inhibited/hyperpolarized by acidification in the range of 0.2 to 0.5 pH or more (15% CO 2 ), the balance being unaffected.…”
Section: Evidence For a Distributed Network Of Central Respiratory Chmentioning
confidence: 99%
“…Because effects of astrocytic opto-depolarization were blocked by MRS 2179, a P2Y1 purinergic receptor antagonist, it was proposed that astrocytes, not neurons, are the cellular proton/CO 2 sensors responsible for respiratory chemoreception, with ATP providing an obligate excitatory signal from astrocytes to neurons via P2Y1 receptors (Gourine et al, 2010). However, later work revealed that RTN neurons are intrinsically chemosensitive (Wang et al, 2013b), and that various P2 receptor antagonists, including MRS 2179, reduced the activation of RTN neurons by CO 2 modestly, at best (Mulkey et al, 2006; Onimaru et al, 2012; Wenker et al, 2012). …”
Section: Co2-sensitivity Of Rtn Neurons: the Role Of Astrocytesmentioning
confidence: 99%
“…Moreover, recent work has shown that the purinergic component of the respiratory drive is at most 30%, a fraction that relies on hemichannel mediated ATP release, and that the actions of endogenous ATP on RTN neurons were not mediated by P2Y1 receptors, leaving open the intriguing possibility P2X receptors play a critical role (Wenker et al, 2012). Furthermore, in newborn rats, RTN chemoreception depends only on the intrinsic chemosensitivity of neurons (Onimaru et al, 2012). In summary, the available data indicate that a component of central chemoreception is mediated by astrocyte ATP that likely acts on P2X receptors in the RTN, demonstrating how ATP neuromodulation has profound effects on RTN neuron function with clear behavioral outcomes in the form of respiratory responses to hypercapnia.…”
Section: Cells and Mechanismsmentioning
confidence: 99%